Limited Genomics Training Among Physicians Remains a Barrier to Genomics-Based Implementation of Precision Medicine - Schaibley, Valerie M.; Ramos, Irma N.; Woosley, Raymond L.; Curry, Steven; Hays, Sean; Ramos, Kenneth S. (Frontiers in Medicine, 2022)
The field of precision medicine has undergone significant growth over the past ten years. Despite increasing applications of clinical genetic and genomic testing, studies consistently report limited knowledge of genetics and genomics among healthcare providers. This study explored barriers to the implementation of precision medicine by surveying physicians working in a large academic medical center. We assessed prior training in genetics, use of genetic testing in the clinic, desire for additional resources in genetics and genomic medicine and perceived barriers to successful integration of precision medicine. Only 20% of respondents reported moderate or extensive training in genetics. Physicians with limited or no training in genetics were less likely to have ordered a genetic test for any purpose. Furthermore, 41% of physicians responded that personal training focused on which genetic tests to order and how to interpret results from specific genetic tests were the most significant barrier to using genetic testing in their clinic. These findings suggest that future efforts to realize the promise of precision medicine should focus on the integration of training programs for non-genetics trained healthcare providers.